Assessment of Steel Structure Connections After Fire Exposure Through Bolt Torque Testing and Dye Penetrant Inspection - Zel Citra; Antonius Antonius; Agung Wahyudi Biantoro (Proceeding of the International Conferences on Engineering Sciences, 2025)
In 2022, a significant fire incident occurred at a steel tower structure in an industrial plant in Lampung, Indonesia, raising serious concerns about the structural integrity and serviceability of the affected steel framework. Fire exposure is known to alter the properties of steel, weaken bolt pretension, and cause defects in welds, underscoring the necessity of thorough post-fire assessments. Nondestructive testing (NDT) methods are crucial in evaluating the safety and stability of structures after fire exposure, as they can detect potential weaknesses without compromising the material further. This study employed two field inspection methods: the bolt torque test and dye penetrant inspection (DPI). A total of 21 bolts (Tor-1 to Tor-21) were tested for their integrity. The results showed that, while all bolts were present, more than half were found to be loosened, indicating the need for re-tightening to restore the specified torque and maintain the required preload for the bolted connections. In addition, 20 welded joints (DP-1 to DP-20) were examined using DPI to detect surface defects. The inspection revealed that 10 welds (50%) exhibited surface defects exceeding 5 mm in length, indicating areas where the welds had been compromised by the fire exposure. Seven welds (35%) were found to be in acceptable condition, while 2 welds (10%) were incomplete or had poor bonding. These findings suggest that while the bolted joints can be restored through corrective re-tightening, the welded joints require more extensive evaluation, local repairs, or even rewelding to ensure their structural integrity. This study highlights the importance of NDT methods in post-fire structural evaluations and recommends periodic inspections and targeted rehabilitation to ensure the long-term reliability and safety of industrial steel structures.